Positive electrode material precursor, positive electrode material, preparation method thereof, and sodium ion battery

By designing the heterostructured cathode material of O3 phase core and P2 phase shell, the lack of cyclic stability and specific capacity of sodium ion battery cathode material is solved, and efficient electrochemical performance is achieved, and suitable for industrial production.

JP2025503978AActive Publication Date: 2025-02-06JINGMEN GEM NEW MATERIAL CO LTD +1

Patent Information

Application Number
JP2024544489
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2022-08-26
Publication Date
2025-02-06
Estimated Expiration
2042-08-26

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the cyclic stability and specific capacity of the positive electrode material of sodium ion battery, especially the structural unstable layered P2 and O3 phase materials during charging and discharging, resulting in challenges in large-scale applications.

Method used

The heterostructured cathode material is used to control the composition and morphology of the core and shell layer, and combine the sparse structure of the sheet-like primary particles to form the cathode material of the O3 phase core and P2 phase shell layer. The synergistic effect of the high capacity of the O3 phase and the stable interface layer of the P2 phase is used to improve electrochemical performance.

Benefits of technology

The high specific capacity and high cycle stability of the cathode material are achieved, and are suitable for industrial large-scale production, simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503978000001_ABST
    Figure 2025503978000001_ABST
Patent Text Reader

Abstract

The present disclosure discloses a positive electrode material precursor, a positive electrode material, a method for preparing the same, and a sodium-ion battery. The positive electrode material precursor includes a core and a shell surrounding the core, the core being made of Ni x Fe y Mn 1-x-y (OH)2, where 0.2≦x≦0.7 and 0.2≦y≦0.5, and the shell is M a Mn 1-a (OH)2, where M is nickel or iron, 0.05≦a≦0.7, and the core and shell are both deposited with flaky primary particles. The cathode material precursor of the present application can obtain a heterostructure cathode material having an O3 phase core and a P2 phase shell by controlling the components of the core and shell and combining them with a sparse structure deposited with flaky primary particles, and the synergistic effect of the two-phase structure can achieve both high capacity and high cycle stability, further improving the electrochemical performance of sodium ion batteries. In addition, the preparation method of the cathode material of the present application is simple, low cost, and suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The embodiments of the present application relate to the technical field of battery production and manufacturing, such as a positive electrode material precursor, a positive electrode material, a preparation method thereof, and a sodium ion battery. [Background technology]

[0002] Sodium element, which has chemical properties similar to lithium, is not only abundant in resource reserves but also widely distributed, so sodium ion batteries are considered to be the most promising secondary batteries to be widely applied in the field of large-scale energy storage, replacing lithium ion batteries. At the same time, compared with lithium ion batteries, sodium ion batteries have more cost advantages, do not contain toxic heavy metals, have a simpler battery structure, and are easier to recover and reuse, so they have more potential for sustainable development.

[0003] However, because sodium ions have a larger radius than lithium ions, the positive electrode material faces complex multiple phase transitions during charging and discharging, and is more unstable in structure compared with lithium ion batteries, and its specific capacity is also lower than that of lithium ion batteries. At present, layered positive electrode materials are usually adopted as the positive electrode material of sodium ion batteries, and according to the difference in sodium ion coordination environment, the layered positive electrode material is mainly divided into P2 phase and O3 phase. Among them, P2 phase is a sodium-deficient compound with open prismatic channels, which can provide rapid ion conductivity and high structural stability, but its capacity is low. On the other hand, O3 phase has the advantage of high specific capacity, but poor structural stability leads to poor cycle stability. Both cannot achieve high structural stability and high specific capacity at the same time. Therefore, how to simultaneously improve the cycle stability and specific capacity of sodium ion batteries is an important problem facing the large-scale application of sodium ion batteries.

[0004] CN108987708A discloses a positive electrode material for a sodium ion battery, a preparation method thereof and a sodium ion battery, and a P2 phase Na 0.67 Ni0.167 Co 0.167 Mn 0.67 The ZrO2 substrate is coated with one layer, and the mass of the coating layer is 1-5% of the mass of the substrate material. Nickel salt, cobalt salt and manganese salt are co-precipitated with Na2CO3 and ammonia water complexing agent to obtain spherical particle precursors, which are then calcined to obtain the substrate material Na 0.67 Ni 0.167 Co 0.167 Mn 0.67 O2 is obtained, the substrate is mixed with Zr(C3H7O)4, the solvent is evaporated, and a sodium ion positive electrode material coated with ZrO2 is obtained. This method requires that the solvent is evaporated to dryness during coating, which makes the treatment process complicated and unenvironmental.

[0005] CN113921809A discloses a positive electrode material for P2-type layered sodium ion battery and its preparation method, in which Na ions are located in the middle of the transition metal layer and form an alkali metal layer, and Na + The site is co-doped with the transition metal site to improve the electrochemical performance of the material. The chemical formula of the positive electrode material is Na 0.67-x M x Mn 1-y N y O2, M=Zn, Al, Mg, K, Ca, Li, N=Fe, Cr, V, Ni, Ti, Cu, Nb, Co. This method uses the sol-gel method to quantitatively dope trace elements and realize intermolecular doping, but it still has a P2 single-phase structure, the specific capacity is not high, and the sol-gel method is only applicable to laboratory preparation and not to large-scale production.

[0006] CN113292113A discloses an O3-phase layered oxide positive electrode material for sodium-ion batteries and a method for preparing the same, which includes dissolving and mixing a transition metal salt and a soluble sodium salt in deionized water to obtain a mixed salt solution, spraying and pyrolyzing the mixed salt solution to obtain a sodium-containing oxide precursor, and pressing the sodium-containing oxide precursor into a sheet shape and then high-temperature solid-state sintering to obtain an O3-phase layered oxide positive electrode material. The layered positive electrode material obtained by the method still has a single-phase structure, and the problem of the positive electrode material being prone to interlayer slippage during charging and discharging of the battery and poor structural stability cannot be solved.

[0007] Therefore, how to simultaneously improve the cycle stability and specific capacity of the positive electrode material of the sodium ion battery while simplifying the preparation process and facilitating industrialized large-scale production is very important for the realization of large-scale application of the sodium ion battery. Summary of the Invention [Problem to be solved by the invention]

[0008] The following is a general summary of the subject matter described in this document, which is not intended to limit the scope of the claims.

[0009] The embodiments of the present application provide a positive electrode material precursor, a positive electrode material, a preparation method thereof and a sodium ion battery, in which the positive electrode material precursor can obtain a heterostructure positive electrode material having an O3 phase core and a P2 phase shell by controlling the components of the core and shell and combining with a sparse structure deposited by flaky primary particles, and further realize the effect of simultaneously improving the cycle stability and specific capacity of the positive electrode material of a sodium ion battery. [Means for solving the problem]

[0010] In aspect 1, an embodiment of the present application is a cathode material precursor, comprising: The positive electrode material precursor includes a core and a shell surrounding the core, and the core is made of Ni x Fe y Mn1-x-y (OH)2, where 0.2≦x≦0.7 and 0.2≦y≦0.5, and the shell is M a Mn 1-a (OH)2, where M is nickel or iron, and 0.05≦a≦0.7, and the core and the shell are both deposited with flake-shaped primary particles; A positive electrode material precursor is provided.

[0011] In the present application, the core and shell of the positive electrode material precursor have different components, and both the core and shell are sparse structures deposited by flaky primary particles, which later contributes to the diffusion of sodium ions into the interior. The components of the core and shell of the positive electrode material precursor are controlled and combined with the sparse structures deposited by flaky primary particles, which later contributes to obtaining a heterostructure positive electrode material having an O3 phase core and a P2 phase shell, in which the O3 phase core provides high capacity, and the P2 phase shell forms a stable interface layer, and the synergistic effect of the two-phase structure achieves the effect of achieving both specific capacity and cycle stability, thereby significantly improving the electrochemical performance of the positive electrode material. Note that the sparse structures of the core and shell deposited by flaky primary particles in the present application means that the morphology of the subunits of the core and shell is flaky, which is different from the layered structure defined by the crystal phase, and the core and shell are both sparse structures, which are also different from the layered structure.

[0012] In the present application, the positive electrode material precursor is Ni x Fe y Mn 1-x-y (OH)2@M a Mn 1-a (OH)2, which means M a Mn 1-a (OH)2 is Ni x Fe y Mn 1-x-y The outer surface of (OH)2 is coated with

[0013] The cathode material precursor of the present application, by controlling the components of the core and shell and combining them with the sparse structure deposited by the flaky primary particles, promotes the subsequent formation of a heterostructure cathode material having an O3 phase core and a P2 phase shell, thereby simultaneously improving the cycle stability and specific capacity of the cathode material for sodium ion batteries.

[0014] In one preferred technical solution of the present application, the morphology of the core in the positive electrode material precursor includes a spherical or near-spherical shape.

[0015] Preferably, the particle size of the core in the positive electrode material precursor is 2 to 4.5 μm, and may be, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or 4.5 μm, but is not limited to the recited values, and other unrecited values ​​within the numerical range also apply.

[0016] Preferably, the morphology of the positive electrode material precursor comprises a spherical or near-spherical shape. Preferably, the particle size of the positive electrode material precursor is 2.5 to 4.5 μm, and may be, for example, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or 4.5 μm, but is not limited to the recited values, and other unrecited values ​​within the range apply as well.

[0017] In the present application, the core particle size of the positive electrode material precursor and the particle size of the positive electrode material precursor both refer to the average particle size.

[0018] In aspect 2, the present embodiment comprises: Injecting a first metal salt mixed solution, a complexing agent solution and a precipitant solution into a reactor at the same time, and performing a primary co-precipitation reaction during the injection process to obtain a core of a positive electrode material precursor; and then injecting a second metal salt mixed solution, the complexing agent solution and the precipitant solution into the reactor at the same time, and performing a secondary co-precipitation reaction during the injection process to obtain the positive electrode material precursor. A method for preparing the cathode material precursor of embodiment 1 is provided.

[0019] In the present application, when the primary coprecipitation reaction is carried out, the first metal salt solution, the complexing agent solution, and the precipitant solution are simultaneously injected into a reactor at a constant flow rate, and the primary coprecipitation reaction is carried out while the first coprecipitation reaction is being carried out, and when the injection of each component is stopped, the primary coprecipitation reaction is terminated, and the coprecipitation reaction is not started after all the first metal salt solution, the complexing agent solution, and the precipitant solution required are put into the reactor. Similarly, the operation process of the secondary coprecipitation reaction in the present application is the same as the operation process of the primary coprecipitation reaction. In other words, the primary coprecipitation reaction and the secondary coprecipitation reaction in the present application are both continuous injection and continuous reaction processes.

[0020] The present application employs a stepwise co-precipitation process of continuous injection and continuous reaction, which can more effectively control the components of the core and shell of the positive electrode material precursor, and can also more effectively adjust and control the precipitant concentration and complexing agent concentration of the mixed solution in the reactor during the co-precipitation process, thereby adjusting and controlling the balance between the nucleation rate and growth rate of crystals, and further forming a sparse structure in which both the core and shell are deposited with flake-like primary particles.

[0021] In one preferred technical solution of the present application, the first metal salt mixed solution is prepared by mixing a nickel salt, an iron salt, a manganese salt and a solvent.

[0022] Preferably, the total concentration of metal ions in the first metal salt mixed solution is 1 to 4 mol / L, and may be, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L, but is not limited to the recited values, and other unrecited values ​​within the numerical range also apply.

[0023] Preferably, the molar ratio of the nickel salt, the iron salt and the manganese salt is x:y:(1-xy), where 0.2≦x≦0.7 and 0.2≦y≦0.5, for example, x may be 0.2, 0.3, 0.4, 0.5, 0.6 or 0.7 and y may be 0.2, 0.3, 0.4 or 0.5.

[0024] Preferably, the nickel salt comprises any one of nickel sulfate, nickel chloride or nickel nitrate.

[0025] Preferably, the iron salt comprises ferrous sulfate or ferrous chloride. Preferably, the manganese salt comprises any one of manganese sulfate, manganese chloride or manganese nitrate.

[0026] Preferably, the solvent comprises deionized water. Preferably, the concentration of the complexing agent is 1 to 3 mol / L, and may be, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, but is not limited to the recited values, and other unrecited values ​​within the numerical range apply as well.

[0027] Preferably, the complexing agent comprises an aqueous ammonia complexing agent. In the present application, an ammonia water complexing agent solution is prepared by mixing ammonia water and deionized water.

[0028] Preferably, the concentration of the precipitant is 1 to 3 mol / L, and may be, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, but is not limited to the recited values, and other unrecited values ​​within the numerical range apply as well.

[0029] Preferably, the precipitating agent comprises an alkaline solution. Preferably, the alkaline solution comprises a sodium hydroxide solution or a potassium hydroxide solution.

[0030] In this application, the precipitant solution is prepared by dissolving the precipitant particles in deionized water. As one preferred technical solution of the present application, in the primary coprecipitation reaction, the first metal salt mixed solution is injected into the reactor at a flow rate of 8 to 12 kg / h, which may be, for example, 8 kg / h, 8.5 kg / h, 9 kg / h, 9.5 kg / h, 10 kg / h, 10.5 kg / h, 11 kg / h, 11.5 kg / h or 12 kg / h, but is not limited to the recited values, and other unrecited values ​​within the numerical range also apply.

[0031] Preferably, in the primary co-precipitation reaction, the complexing agent solution is injected into the reactor at a flow rate of 1-3 kg / h, which may be, for example, 1 kg / h, 1.5 kg / h, 2 kg / h, 2.5 kg / h or 3 kg / h, but is not limited to the recited values, and other unrecited values ​​within the numerical ranges also apply.

[0032] Preferably, in the primary co-precipitation reaction, the precipitant solution is injected into the reactor at a flow rate of 2.4-3 kg / h, which may be, for example, 2.4 kg / h, 2.5 kg / h, 2.6 kg / h, 2.7 kg / h, 2.8 kg / h, 2.9 kg / h or 3 kg / h, but is not limited to the recited values, and other unrecited values ​​within the numerical ranges also apply.

[0033] In the present invention, the flow rate of the first metal salt mixed solution in the primary coprecipitation reaction is limited to 8-12 kg / h, the flow rate of the complexing agent solution is limited to 1-3 kg / h, and the flow rate of the precipitating agent solution is limited to 2.4-3 kg / h. The reason for this is that the flow rates of the first metal salt solution, the complexing agent solution and the precipitating agent solution are coordinated to maintain the pH stability of the primary coprecipitation reaction (i.e., the stability of the precipitating agent concentration in the solution in the reactor) and the stability of the complexing agent concentration in the solution in the reactor, so as to maintain the stability of the system during the entire process of the primary coprecipitation reaction and to contribute to the formation of a sparse core structure deposited by flaky primary particles. Coprecipitation is carried out after all the required first metal salt mixed solution, the complexing agent solution and the precipitating agent solution are all introduced into the reactor, so as to avoid the problem that the pH and the complexing agent concentration of the coprecipitation reaction gradually decrease due to the continuous consumption of the precipitating agent and the complexing agent, and the stability of the system is poor, so that the components and morphology of the core cannot be precisely controlled.

[0034] Preferably, the primary co-precipitation reaction is carried out at 40 to 60°C, which may be, for example, 40°C, 45°C, 50°C, 55°C, or 60°C, but is not limited to the recited values, and other unrecited values ​​within the range apply as well.

[0035] Preferably, during the primary co-precipitation reaction, the pH of the solution in the reaction vessel is 9.5 to 11, and may be, for example, 9.5, 10, 10.5 or 11, but is not limited to the recited values, and other unrecited values ​​within the range also apply.

[0036] Preferably, during the primary co-precipitation reaction, the concentration of the complexing agent in the solution in the reaction apparatus is 7 to 11 g / L, and may be, for example, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L, 10 g / L, 10.5 g / L or 11 g / L, but is not limited to the recited values, and other unrecited values ​​within the numerical range also apply.

[0037] In the present invention, by coordinating the flow rates of the first metal salt solution, the complexing agent solution and the precipitant solution, the pH of the primary coprecipitation reaction can be controlled to 9.5-11, and the complexing agent concentration can be controlled to 7-11 g / L, where the pH is mainly used to adjust and control the crystal nucleation rate in the primary coprecipitation reaction, and the complexing agent concentration is mainly used to adjust and control the crystal growth rate in the primary coprecipitation reaction, so that by controlling the pH and the complexing agent concentration within a suitable range, the crystal nucleation rate and the crystal growth rate can be dynamically balanced, which is conducive to obtaining a sparse core structure deposited by flaky primary particles, and effectively controls the uniformity of the core particle size.

[0038] Preferably, the primary co-precipitation reaction is carried out under stirring. Preferably, the stirring speed of the primary coprecipitation reaction is 300 to 380 r / min, and may be, for example, 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min, 350 r / min, 360 r / min, 370 r / min or 380 r / min, but is not limited to the listed numerical values, and other unlisted numerical values ​​within the numerical range also apply.

[0039] In the present application, the stirring rotation speed of the primary coprecipitation reaction is limited to 300-380 r / min. If the rotation speed is lower than 300 r / min, the secondary particle aggregation phenomenon becomes severe and the sphericity is poor. If the rotation speed is higher than 380 r / min, the particle size does not grow easily during the coprecipitation process and fine powder is easily generated, which affects the electrochemical performance of the positive electrode material.

[0040] In the present invention, by adjusting and controlling the pH of the solution in the reactor and the concentration of the complexing agent during the primary coprecipitation reaction process and combining it with an appropriate stirring rotation speed, it is possible to better obtain spherical / spherical cores deposited with flaky primary particles.

[0041] Preferably, the time for the primary coprecipitation reaction is 60 to 90 hours, and may be, for example, 60 hours, 65 hours, 70 hours, 75 hours, 80 hours, 85 hours or 90 hours, but is not limited to the recited values, and other unrecited values ​​within the range of values ​​also apply.

[0042] Preferably, before the primary coprecipitation reaction, deionized water, the complexing agent solution and the precipitating agent solution are first added to the reaction apparatus to prepare a base solution for the primary coprecipitation reaction.

[0043] In this application, a certain amount of deionized water, complexing agent solution and precipitant solution are added into the reactor to form a base solution, ensuring that the nucleation and growth of crystals are carried out in the solution system, and maintaining the stability of the subsequent co-precipitation reaction system, the pH of the base solution is 10.5-11, and the concentration of the complexing agent is 7-10. When a 200L reactor is used as the reactor, the total amount of the base solution may be 100L.

[0044] In one preferred technical solution of the present application, the second metal salt mixed solution is prepared by mixing a nickel salt, a manganese salt and a solvent, or the second metal salt mixed solution is prepared by mixing an iron salt, a manganese salt and a solvent.

[0045] Preferably, the total concentration of metal ions in the second metal salt mixed solution is 1 to 4 mol / L, and may be, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L, but is not limited to the recited values, and other unrecited values ​​within the numerical range also apply.

[0046] Preferably, the molar ratio of the nickel salt to the manganese salt is a:(1-a), or the molar ratio of the iron salt to the manganese salt is a:(1-a), where 0.05≦a≦0.7, and may be, for example, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or 0.7, but is not limited to the recited values, and other unrecited values ​​within the numerical ranges also apply.

[0047] Preferably, the nickel salt comprises any one of nickel sulfate, nickel chloride or nickel nitrate.

[0048] Preferably, the iron salt comprises ferrous sulfate or ferrous chloride. Preferably, the manganese salt comprises any one of manganese sulfate, manganese chloride or manganese nitrate.

[0049] Preferably, the solvent comprises deionized water. Preferably, in the secondary coprecipitation reaction, the second metal salt mixed solution is injected into the reactor at a flow rate of 8 to 12 kg / h, which may be, for example, 8 kg / h, 8.5 kg / h, 9 kg / h, 9.5 kg / h, 10 kg / h, 10.5 kg / h, 11 kg / h, 11.5 kg / h or 12 kg / h, but is not limited to the recited values, and other unrecited values ​​within the numerical range also apply.

[0050] Preferably, in the secondary co-precipitation reaction, the complexing agent solution is injected into the reactor at a flow rate of 1-3 kg / h, which may be, for example, 1 kg / h, 1.5 kg / h, 2 kg / h, 2.5 kg / h or 3 kg / h, but is not limited to the recited values, and other unrecited values ​​within the numerical ranges also apply.

[0051] Preferably, in the secondary co-precipitation reaction, the precipitant solution is injected into the reactor at a flow rate of 2.4-3 kg / h, which may be, for example, 2.4 kg / h, 2.5 kg / h, 2.6 kg / h, 2.7 kg / h, 2.8 kg / h, 2.9 kg / h or 3 kg / h, but is not limited to the recited values, and other unrecited values ​​within the numerical range apply as well.

[0052] Similarly, the present application can maintain the stability of pH and the stability of complexing agent concentration in the secondary coprecipitation reaction by coordinating the flow rates of the second metal salt solution, the complexing agent solution and the precipitating agent solution, thereby maintaining the stability of the system during the entire process of the secondary coprecipitation reaction, and contributing to the formation of a sparse shell structure deposited by flake-like primary particles on the outer surface of the core. The required second metal salt mixed solution, the complexing agent solution and the precipitating agent solution are all put into the reactor before coprecipitation is carried out, avoiding the problem that the pH and the complexing agent concentration of the coprecipitation reaction gradually decrease due to the continuous consumption of the precipitating agent and the complexing agent, and the stability of the system is poor, so that the composition and morphology of the core cannot be precisely controlled. In addition, the complexing agent solution and the precipitating agent solution adopted in the secondary coprecipitation reaction are the same as the complexing agent solution and the precipitating agent solution adopted in the primary coprecipitation reaction, respectively.

[0053] Preferably, the secondary co-precipitation reaction is carried out at 40 to 60°C, and may be, for example, 40°C, 45°C, 50°C, 55°C, or 60°C, but is not limited to the recited values, and other unrecited values ​​within the range apply as well.

[0054] Preferably, during the secondary co-precipitation reaction, the pH of the solution in the reaction vessel is 8.5 to 11, and may be, for example, 8.5, 9, 9.5, 10, 10.5 or 11, but is not limited to the recited values, and other unrecited values ​​within the range also apply.

[0055] Preferably, during the secondary coprecipitation reaction, the concentration of the complexing agent in the solution in the reactor is 8 to 12 g / L, and may be, for example, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L, 10 g / L, 10.5 g / L or 11 g / L, but is not limited to the recited values, and other unrecited values ​​within the numerical range also apply.

[0056] Similarly, in the present application, pH is mainly used to adjust and control the nucleation rate of crystals in the secondary coprecipitation reaction, and the concentration of complexing agent is mainly used to adjust and control the growth rate of crystals in the secondary coprecipitation reaction, so that the pH and the concentration of complexing agent can be controlled within a suitable range to adjust and control the nucleation rate of crystals and the growth rate of crystals, which contributes to the formation of a sparse shell structure deposited on the core surface by the flaky primary particles. In the secondary coprecipitation process, the crystal particles on the core surface can be used as seed crystals to grow and form a shell, and in the secondary coprecipitation process, crystal growth is more difficult, so the pH of the secondary coprecipitation is slightly lower than that of the primary coprecipitation, but the concentration of complexing agent is slightly higher than that of the primary coprecipitation.

[0057] Preferably, the secondary coprecipitation reaction is carried out under stirring. Preferably, the stirring speed of the secondary coprecipitation reaction is 250 to 350 r / min, and may be, for example, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min, 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min or 350 r / min, but is not limited to the enumerated values, and other unenumerated values ​​within the numerical range also apply.

[0058] In the present application, the stirring rotation speed of the secondary coprecipitation reaction is limited to 250-350 r / min. If the rotation speed is lower than 250 r / min, the secondary particle aggregation phenomenon becomes severe, the sphericity becomes poor, and the coating becomes non-uniform. If the rotation speed is higher than 350 r / min, the particle growth rate is limited and fine powder is easily generated, which affects the electrochemical performance of the positive electrode material.

[0059] In the present application, by adjusting and controlling the pH of the solution in the reactor and the concentration of the complexing agent during the secondary coprecipitation reaction process, and by combining with an appropriate stirring rotation speed, the shell deposited by the flaky primary particles can be better obtained, and a spherical / near-spherical positive electrode material precursor can be obtained.

[0060] Preferably, the time for the secondary co-precipitation reaction is 2 to 8 h, and may be, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, but is not limited to the recited values, and other unrecited values ​​within the range of values ​​also apply.

[0061] In a third aspect, the present application provides Prepared with the cathode material precursor according to embodiment 1. A positive electrode material is provided.

[0062] The positive electrode material includes an O3 phase core and a P2 phase shell surrounding the O3 phase core, and the O3 phase core is composed of Na(Ni x Fe y Mn 1-x-y )O2, where 0.2≦x≦0.7 and 0.2≦y≦0.5, and the P2 phase shell is Na b (M a Mn 1-a )O2, where M is nickel or iron, 0.05≦a≦0.7, and 0.67≦b≦0.78, and the O3 phase core and the P2 phase shell are both deposited in flake-like primary particles.

[0063] The cathode material of the present application has a structure in which a P2 shell encases an O3 core, and the advantages of the high capacity of the O3 phase and the high stability of the P2 phase solve the problem of the incompatibility of capacity and stability faced by sodium ion cathode materials at the crystal structure level.In addition, the particle size of the cathode material of the present application is not significantly different from that of the cathode material precursor.

[0064] In the present application, the positive electrode material is Na(Ni x Fe y Mn 1-x-y )O2@Na b (MaM 1-a )O2, which means Na b (MaM 1-a )O2 with Na(Ni x Fe y Mn 1-x-y )O2's outer surface.

[0065] In aspect 4, the present embodiment comprises: mixing a positive electrode material precursor, a dispersant and a sodium source, and then calcining the mixture to obtain the positive electrode material; A method for preparing the cathode material according to embodiment 3 is provided.

[0066] In the present invention, a dispersant is added during the mixing process of the positive electrode material precursor and the sodium source, and at high temperatures, sodium ions are promoted to diffuse into the inside of the positive electrode material precursor particles, and the formation of a positive electrode material structure in which the core is the O3 phase and the shell is the P2 phase is promoted. The preparation method is simple, the cost is low, and it is suitable for large-scale industrial production.

[0067] In one preferred technical solution of the present application, the dispersant comprises polyvinylpyrrolidone. Preferably, the sodium source comprises sodium carbonate.

[0068] Preferably, the positive electrode material precursor, the dispersant and the sodium source are mixed by grinding in a mortar.

[0069] Preferably, the firing temperature is 800 to 1000°C, and may be, for example, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, or 1000°C, but is not limited to the recited values, and other unrecited values ​​within the numerical range apply as well.

[0070] Preferably, the baking time is 12 to 20 h, and may be, for example, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, or 20 h, but is not limited to the recited values, and other unrecited values ​​within the range apply as well.

[0071] In aspect 5, the present embodiment comprises: The cathode material according to embodiment 3 is included. A sodium ion battery is provided.

[0072] The sodium ion battery prepared with the positive electrode material of the present application has significantly improved specific capacity and cycle stability, which further improves the electrochemical performance of the sodium ion battery and promotes the industrialization of the sodium ion battery. Effect of the Invention

[0073] Compared with the related art, the beneficial effects of the embodiments of the present application are as follows: The cathode material precursor according to the embodiment of the present application can obtain a heterostructure cathode material having an O3 phase core and a P2 phase shell by controlling the components of the core and shell, and combining the sparse structure deposited by the flaky primary particles contributes to the diffusion of sodium ions into the interior during the sintering process, in which the O3 phase core provides high capacity, and the P2 phase shell forms a stable interfacial layer, and the synergistic effect of the two-phase structure can achieve both high capacity and high cycle stability, further improving the electrochemical performance of sodium ion batteries. In addition, the preparation method of the cathode material according to the present application is simple, low cost, and suitable for large-scale industrial production.

[0074] Other aspects may be understood upon reading and understanding the drawings and detailed description. The drawings are intended to provide a further understanding of the technical solutions of the embodiments of the present invention, constitute a part of the specification, and are intended to interpret the technical solutions of the present invention together with the embodiments of the present application, but are not intended to limit the technical solutions of the present invention. [Brief description of the drawings]

[0075] [Figure 1] FIG. 2 is an SEM image of a positive electrode material precursor according to Example 1 of the present application. [Diagram 2] FIG. 2 is a SEM image of a cross section of a positive electrode material precursor according to Example 1 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0076] The technical solution of the present application will be further described below through specific embodiments. Those skilled in the art will understand that the above examples are merely for understanding the present application, and are not intended to specifically limit the present application. EXAMPLES

[0077] This embodiment provides a method for preparing a positive electrode material, which includes the following steps: (1) Nickel sulfate, ferrous sulfate, and manganese sulfate were dissolved in deionized water in a molar ratio of 0.25:0.5:0.25 to prepare a first metal salt mixed solution with a total metal ion concentration of 1 mol / L, and ferrous sulfate and manganese sulfate were dissolved in deionized water in a molar ratio of 0.5:0.5 to prepare a second metal salt mixed solution with a total metal ion concentration of 2 mol / L. Simultaneously, an ammonia water complexing agent solution with a concentration of 1 mol / L and a sodium hydroxide solution with a concentration of 2 mol / L were prepared.

[0078] (2) Add deionized water, the ammonia water complexing agent solution obtained in step (1) and sodium hydroxide solution into a 200L reaction vessel to form a base liquid to maintain the stability of the system, where the total volume of the base liquid is 100L, and control the concentration of the ammonia water complexing agent in the base liquid within the range of 9-10g / L, and control the pH within the range of 10.6-11. Then, inject the first metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution into the reaction vessel at the same time with flow rates of 8kg / h, 2kg / h and 2.5kg / h, respectively, and carry out the primary coprecipitation reaction at a temperature of 45°C and a stirring speed of 340r / min for 80h to obtain the core Ni of the positive electrode material precursor with an average particle size of 3.8μm. 0.25 Fe 0.5 Mn 0.25 (OH)2 was obtained, where the pH of the solution in the reaction vessel was maintained within the range of 9.5-10 during the primary coprecipitation reaction, and the complexing agent concentration in the solution in the reaction vessel was maintained within the range of 8-10 g / L.

[0079] (3) The second metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution were simultaneously injected into the reaction vessel at flow rates of 8 kg / h, 2.3 kg / h and 2.4 kg / h, respectively, and the secondary coprecipitation reaction was carried out at a temperature of 45°C and a stirring speed of 280 r / min for 4 hours to obtain the cathode material precursor Ni with an average particle size of 4.2 μm. 0.25 Fe 0.5 Mn 0.25 (OH)2@Fe 0.5 Mn 0.5 (OH)2 was obtained and shown in Figures 1 and 2. Here, the pH of the solution in the reaction vessel was maintained within the range of 9.5-10.5 during the secondary coprecipitation reaction, and the complexing agent concentration in the solution in the reaction vessel was maintained within the range of 9-11 g / L.

[0080] (4) The positive electrode material precursor obtained in step (3), polyvinylpyrrolidone, and sodium carbonate are mixed uniformly in a mortar, and then calcined at a temperature of 800°C for 18 hours to obtain a cathode material having the chemical formula Na(Ni 0.25 Fe 0.5 Mn 0.25 )O2@Na 2 / 3 (Fe 0.5 Mn 0.5 )O2 positive electrode material was obtained. EXAMPLES

[0081] This embodiment provides a method for preparing a positive electrode material, which includes the following steps: (1) Nickel sulfate, ferrous sulfate, and manganese sulfate were dissolved in deionized water in a molar ratio of 1 / 3:1 / 3:1 / 3 to prepare a first metal salt mixed solution with a total metal ion concentration of 1 mol / L, and ferrous sulfate and manganese sulfate were dissolved in deionized water in a molar ratio of 0.7:0.3 to prepare a second metal salt mixed solution with a total metal ion concentration of 2 mol / L. Together with these, an ammonia water complexing agent solution with a concentration of 2 mol / L and a sodium hydroxide solution with a concentration of 2 mol / L were prepared.

[0082] (2) Add deionized water, the ammonia water complexing agent solution obtained in step (1) and sodium hydroxide solution into a 200L reaction vessel to form a base liquid to maintain the stability of the system, where the total volume of the base liquid is 100L, and control the concentration of the ammonia water complexing agent in the base liquid within the range of 7-8g / L, and control the pH within the range of 10.5-11. Then, inject the first metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution into the reaction vessel at the flow rates of 10kg / h, 2.5kg / h and 2.8kg / h, respectively, and carry out the primary coprecipitation reaction at a temperature of 52°C and a stirring speed of 350r / min for 75h to obtain the core Ni of the positive electrode material precursor with an average particle size of 3.6μm. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 was obtained, where the pH of the solution in the reaction vessel was maintained within the range of 9.8-10.6 during the primary coprecipitation reaction, and the concentration of the complexing agent in the solution in the reaction vessel was maintained within the range of 8-10 g / L.

[0083] (3) The second metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution were simultaneously injected into the reaction vessel at flow rates of 10 kg / h, 3 kg / h and 2.6 kg / h, respectively, and the secondary coprecipitation reaction was carried out at a temperature of 52°C and a stirring speed of 300 r / min for 8 hours to obtain the cathode material precursor Ni with an average particle size of 4 μm. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2@Fe0.7 Mn 0.3 (OH)2 was obtained, where the pH of the solution in the reaction vessel was maintained within the range of 9.5-10.5 during the secondary coprecipitation reaction, and the complexing agent concentration in the solution in the reaction vessel was maintained within the range of 9-11 g / L.

[0084] (4) The positive electrode material precursor obtained in step (3), polyvinylpyrrolidone, and sodium carbonate are mixed uniformly in a mortar, and then calcined at a temperature of 900°C for 16 hours to obtain a cathode material having the chemical formula Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )O2@Na 0.7 (Fe 0.7 Mn 0.3 )O2 positive electrode material was obtained. EXAMPLES

[0085] This embodiment provides a method for preparing a positive electrode material, which includes the following steps: (1) Nickel sulfate, ferrous sulfate, and manganese sulfate were dissolved in deionized water in a molar ratio of 0.2:0.5:0.3 to prepare a first metal salt mixed solution having a total metal ion concentration of 3 mol / L, and nickel sulfate and manganese sulfate were dissolved in deionized water in a molar ratio of 0.6:0.4 to prepare a second metal salt mixed solution having a total metal ion concentration of 1 mol / L. Together with these, an ammonia water complexing agent solution having a concentration of 1 mol / L and a sodium hydroxide solution having a concentration of 3 mol / L were prepared.

[0086] (2) Add deionized water, the ammonia water complexing agent solution obtained in step (1) and sodium hydroxide solution into a 200L reaction vessel to form a base liquid to maintain the stability of the system, where the total volume of the base liquid is 100L, and control the concentration of the ammonia water complexing agent in the base liquid within the range of 9-10g / L, and control the pH within the range of 10.6-11. Then, inject the first metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution into the reaction vessel at the same time with flow rates of 12kg / h, 3kg / h and 2.4kg / h, respectively, and carry out the primary coprecipitation reaction at a temperature of 40°C and a stirring speed of 380r / min for 60h, to obtain the core Ni of the positive electrode material precursor with an average particle size of 2μm.0.2 Fe 0.5 Mn 0.3 (OH)2 was obtained, where the pH of the solution in the reaction vessel was maintained within the range of 9.8-11 during the primary coprecipitation reaction, and the complexing agent concentration in the solution in the reaction vessel was maintained within the range of 7-9 g / L.

[0087] (3) The second metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution were simultaneously injected into the reaction vessel at flow rates of 12 kg / h, 3 kg / h and 2.4 kg / h, respectively, and the secondary coprecipitation reaction was carried out at a temperature of 40°C and a stirring speed of 350 r / min for 2 h to obtain the cathode material precursor Ni with an average particle size of 2.5 μm. 0.2 Fe 0.5 Mn 0.3 (OH)2@Ni 0.6 Mn 0.4 (OH)2 was obtained, where the pH of the solution in the reaction vessel was maintained within the range of 8.5-9.5 during the secondary coprecipitation reaction, and the concentration of the complexing agent in the solution in the reaction vessel was maintained within the range of 8-10 g / L.

[0088] (4) The positive electrode material precursor obtained in step (3), polyvinylpyrrolidone, and sodium carbonate are mixed uniformly in a mortar, and then calcined at a temperature of 1000°C for 12 hours to obtain a cathode material having the chemical formula Na(Ni 0.2 Fe 0.5 Mn 0.3 )O2@Na 0.78 (Ni 0.6 Mn 0.4 )O2 positive electrode material was obtained. EXAMPLES

[0089] This embodiment provides a method for preparing a positive electrode material, which includes the following steps: (1) Nickel sulfate, ferrous sulfate, and manganese sulfate were dissolved in deionized water in a molar ratio of 0.7:0.2:0.1 to prepare a first metal salt mixed solution having a total metal ion concentration of 4 mol / L, and ferrous sulfate and manganese sulfate were dissolved in deionized water in a molar ratio of 0.1:0.9 to prepare a second metal salt mixed solution having a total metal ion concentration of 4 mol / L. Together with these, an ammonia water complexing agent solution having a concentration of 1 mol / L and a sodium hydroxide solution having a concentration of 3 mol / L were prepared.

[0090] (2) Add deionized water, the ammonia water complexing agent solution obtained in step (1) and sodium hydroxide solution into a 200L reaction vessel to form a base liquid to maintain the stability of the system, where the total volume of the base liquid is 100L, and control the concentration of the ammonia water complexing agent in the base liquid within the range of 9-10g / L, and control the pH within the range of 10.6-11. Then, inject the first metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution into the reaction vessel at the flow rates of 11kg / h, 1kg / h and 3kg / h, respectively, and carry out the primary coprecipitation reaction at a temperature of 60°C and a stirring speed of 300r / min for 90h to obtain the core Ni of the positive electrode material precursor with an average particle size of 4μm. 0.7 Fe 0.2 Mn 0.1 (OH)2 was obtained, where the pH of the solution in the reaction vessel was maintained within the range of 9.5-11 during the primary coprecipitation reaction, and the concentration of the complexing agent in the solution in the reaction vessel was maintained within the range of 9-11 g / L.

[0091] (3) The second metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution were simultaneously injected into the reaction vessel at flow rates of 11 kg / h, 1 kg / h and 3 kg / h, respectively, and the secondary coprecipitation reaction was carried out at a temperature of 60°C and a stirring speed of 250 r / min for 6 hours to obtain the cathode material precursor Ni with an average particle size of 4.5 μm. 0.7 Fe 0.2 Mn 0.1 (OH)2@Fe 0.1 Mn 0.9 (OH)2 was obtained, where the pH of the solution in the reaction vessel was maintained within the range of 10-11 during the secondary coprecipitation reaction, and the concentration of the complexing agent in the solution in the reaction vessel was maintained within the range of 10-12 g / L.

[0092] (4) The positive electrode material precursor obtained in step (3), polyvinylpyrrolidone, and sodium carbonate are mixed uniformly in a mortar, and then calcined at a temperature of 800°C for 20 hours to obtain a cathode material having the chemical formula Na(Ni 0.7 Fe 0.2 Mn 0.1 )O2@Na 2 / 3 (Fe 0.1 Mn 0.9 )O2 positive electrode material was obtained. EXAMPLES

[0093] The difference between this embodiment and Example 1 is that the flow rate of the sodium hydroxide solution in step (2) is 3.5 kg / h, and the pH of the solution in the reaction vessel is maintained within the range of 11.5-12.5 during the primary coprecipitation reaction. The remaining process parameters and operating conditions are the same as those of Example 1. EXAMPLES

[0094] The present embodiment is different from Example 1 in that the flow rate of the sodium hydroxide solution in step (2) is 2 kg / h, and the pH of the solution in the reaction vessel is maintained within the range of 8-9.2 during the primary coprecipitation reaction. The remaining process parameters and operating conditions are the same as those in Example 1. EXAMPLES

[0095] The present embodiment is different from Example 1 in that the flow rate of the ammonia water complexing agent solution in step (2) is 4 kg / h, and the complexing agent concentration in the solution in the reaction vessel is maintained within the range of 11.5 to 13.5 during the primary coprecipitation reaction process. The remaining process parameters and operating conditions are the same as those in Example 1. EXAMPLES

[0096] The difference between this embodiment and embodiment 1 is that the flow rate of the ammonia water complexing agent solution in step (2) is 0.5 kg / h, and the complexing agent concentration in the solution in the reaction vessel is maintained within the range of 5 to 6.5 during the primary coprecipitation reaction process. The remaining process parameters and operating conditions are the same as those in embodiment 1. EXAMPLES

[0097] The difference between this embodiment and embodiment 1 is that the flow rate of the sodium hydroxide solution in step (3) is 3.5 kg / h, and the pH of the solution in the reaction vessel is maintained within the range of 11.7-12.5 during the secondary coprecipitation reaction. The remaining process parameters and operating conditions are the same as those of embodiment 1. EXAMPLES

[0098] The present embodiment is different from Example 1 in that the flow rate of the sodium hydroxide solution in step (3) is 2 kg / h, and the pH of the solution in the reaction vessel is maintained within the range of 6.5-8 during the secondary coprecipitation reaction. The remaining process parameters and operating conditions are the same as those in Example 1. EXAMPLES

[0099] The difference between this embodiment and embodiment 1 is that the flow rate of the ammonia water complexing agent solution in step (3) is 4.5 kg / h, and the complexing agent concentration in the solution in the reaction vessel during the primary coprecipitation reaction is maintained within the range of 12.5 to 14.5; the remaining process parameters and operating conditions are the same as those in embodiment 1. EXAMPLES

[0100] The present embodiment is different from Example 1 in that the flow rate of the ammonia water complexing agent solution in step (3) is 0.3 kg / h, and the complexing agent concentration in the solution in the reaction vessel is maintained within the range of 6 to 7.5 during the primary coprecipitation reaction. The remaining process parameters and operating conditions are the same as those in Example 1. EXAMPLES

[0101] The difference between this example and Example 1 is that the addition of polyvinylpyrrolidone in step (4) is omitted, while the remaining process parameters and operating conditions are the same as those of Example 1. Comparative Example 1

[0102] The difference between this comparative example and Example 1 is that the first metal salt mixed solution, the ammonia water complexing agent solution, and the sodium hydroxide solution required in step (2) were all placed in the reactor before the primary coprecipitation reaction was carried out, while the remaining process parameters and operating conditions were the same as those of Example 1.

[0103] The difference between this comparative example and Example 1 is that the second metal salt mixed solution, the ammonia water complexing agent solution and the sodium hydroxide solution required in step (3) were all placed in the reactor before the secondary coprecipitation reaction was carried out; the remaining process parameters and operating conditions were the same as those of Example 1.

[0104] The positive electrode materials prepared in Examples 1 to 13 and Comparative Examples 1 and 2 were assembled into coin batteries, and electrochemical performance tests were carried out.

[0105] The performance test parameters are as follows: (1) Reversible capacity test: Initial charge / discharge curves of a half-cell at a current density of 12.5 (0.1C), and the voltage range was 2-4.2V.

[0106] (2) Cycle performance test: The half-cell was cycled 100 times at 1C, with a voltage range of 2-4.2V.

[0107] The positive electrode materials prepared in Examples 1 to 13 and Comparative Examples 1 to 2 were assembled into coin batteries, and their electrochemical performance test structures are shown in Table 1.

[0108] [Table 1]

[0109] The data in Table 1 reveals the following: (1) The positive electrode materials prepared in Examples 1 to 4 have high reversible capacity and excellent cycle performance, which means that the preparation method of the present application can be used to obtain a positive electrode material with a heterostructure having an O3 core and a P2 shell, in which the O3 core provides high capacity and the P2 shell forms a stable interface layer. The synergistic effect of the two-phase structure achieves both high capacity and high cycle stability, and further improves the electrochemical performance of sodium-ion batteries.

[0110] (2) The capacity and cycle performance of the positive electrode materials prepared in Examples 5 to 8 are all lower than that of Example 1. The reason is that the flow rate of the precipitant in the primary coprecipitation is too high in Example 5, the flow rate of the precipitant in the primary coprecipitation is too low in Example 6, the flow rate of the complexing agent in the primary coprecipitation is too high in Example 7, and the flow rate of the complexing agent in the primary coprecipitation is too low in Example 8. This means that the present application can better maintain the stability of the system during the entire primary coprecipitation reaction by controlling the flow rates of the precipitant and complexing agent in the primary coprecipitation within appropriate ranges, respectively, and contribute to the formation of a sparse core structure deposited by flaky primary particles, thereby further improving the electrochemical performance of the positive electrode materials.

[0111] (3) The capacity and cycle performance of the positive electrode materials prepared in Examples 9 to 12 are all lower than that of Example 1, because the flow rate of the precipitant in the secondary coprecipitation is too high in Example 9, the flow rate of the precipitant in the secondary coprecipitation is too low in Example 10, the flow rate of the complexing agent in the secondary coprecipitation is too high in Example 11, and the flow rate of the complexing agent in the secondary coprecipitation is too low in Example 12. This means that the present application maintains the stability of the system throughout the entire secondary coprecipitation reaction process by controlling the flow rates of the precipitant and complexing agent in the secondary coprecipitation within appropriate ranges, respectively, and contributes to the formation of a sparse shell structure deposited by flaky primary particles on the outer surface of the core, thereby further improving the electrochemical performance of the positive electrode material.

[0112] (4) The capacity and cycle performance of the positive electrode material prepared in Example 13 are both lower than those of Example 1. This is because in Example 13, the addition of a dispersant is omitted in the firing process, and the diffusion of sodium ions into the inside of the positive electrode material precursor particles cannot be effectively promoted in the firing process, which affects the electrochemical performance of the positive electrode material.

[0113] (5) The capacity and cycle performance of the positive electrode materials prepared in Comparative Examples 1 and 2 are all lower than that of Example 1. This is because in Comparative Example 1, the first metal salt mixed solution, the complexing agent solution, and the precipitant solution are all placed in the reaction kettle to carry out the primary precipitation reaction, and in Comparative Example 2, the second metal salt mixed solution, the complexing agent solution, and the precipitant solution are all placed in the reaction kettle to carry out the secondary precipitation reaction. As a result, the pH stability and the complexing agent concentration stability of the primary coprecipitation reaction and the secondary coprecipitation reaction cannot be effectively maintained, and the rates of crystal nucleation and crystal growth in the primary coprecipitation reaction and the secondary coprecipitation reaction cannot be adjusted or controlled. As a result, a positive electrode material precursor having a sparse structure deposited by flaky primary particles cannot be obtained, which further affects the electrochemical performance of the positive electrode material.

[0114] The applicant declares that the above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto, and that any modification or replacement that a person skilled in the art can easily conceive within the technical scope disclosed in the present application should be understood to be included in the scope of protection and disclosure of the present application.

Claims

1. A positive electrode material precursor, The positive electrode material precursor includes a core and a shell surrounding the outer periphery of the core, and the core is made of Ni x Fe y Mn 1-x-y (OH) 2 where 0.2≦x≦0.7 and 0.2≦y≦0.5, and the shell is M a Mn 1-a (OH) 2 wherein M is nickel or iron, 0.05≦a≦0.7, and the core and the shell are both deposited with flake-shaped primary particles; Positive electrode material precursor.

2. The morphology of the core in the positive electrode material precursor includes a spherical or near-spherical shape; The cathode material precursor of claim 1 .

3. The particle size of the core in the positive electrode material precursor is 2 to 4.5 μm; The positive electrode material precursor according to claim 1 or 2.

4. The morphology of the positive electrode material precursor includes a spherical or near-spherical shape. The positive electrode material precursor according to any one of claims 1 to 3.

5. The particle size of the positive electrode material precursor is 2.5 to 4.5 μm. The positive electrode material precursor according to any one of claims 1 to 4.

6. Injecting a first metal salt mixed solution, a complexing agent solution and a precipitant solution into a reactor at the same time, and performing a primary co-precipitation reaction during the injection process to obtain a core of a positive electrode material precursor; and then injecting a second metal salt mixed solution, the complexing agent solution and the precipitant solution into the reactor at the same time, and performing a secondary co-precipitation reaction during the injection process to obtain the positive electrode material precursor. A method for preparing the positive electrode material precursor according to any one of claims 1 to 5.

7. The first metal salt mixed solution is prepared by mixing a nickel salt, an iron salt, a manganese salt, and a solvent; The preparation method according to claim 6.

8. The total concentration of metal ions in the first metal salt mixed solution is 1 to 4 mol / L; 8. The preparation method according to claim 6 or 7.

9. the molar ratio of the nickel salt, the iron salt and the manganese salt is x:y:(1-xy), where 0.2≦x≦0.7 and 0.2≦y≦0.5; The preparation method according to any one of claims 6 to 8.

10. The nickel salt includes any one of nickel sulfate, nickel chloride, and nickel nitrate; Preferably, the iron salt comprises ferrous sulfate or ferrous chloride; Preferably, the manganese salt comprises any one of manganese sulfate, manganese chloride or manganese nitrate; Preferably, the solvent comprises deionized water; Preferably, the concentration of the complexing agent is 1 to 3 mol / L; Preferably, the complexing agent comprises an ammonia water complexing agent; Preferably, the concentration of the precipitant is 1 to 3 mol / L; Preferably, the precipitating agent comprises an alkaline solution; Preferably, the alkaline solution comprises a sodium hydroxide solution or a potassium hydroxide solution. The preparation method according to any one of claims 6 to 9.

11. In the primary coprecipitation reaction, the first metal salt mixed solution is injected into the reactor at a flow rate of 8 to 12 kg / h; Preferably, in the primary coprecipitation reaction, the complexing agent solution is injected into the reactor at a flow rate of 1 to 3 kg / h; Preferably, in the primary coprecipitation reaction, the precipitant solution is injected into the reactor at a flow rate of 2.4 to 3 kg / h; Preferably, the primary coprecipitation reaction is carried out at 40 to 60° C. Preferably, during the primary co-precipitation reaction, the pH of the solution in the reactor is 9.5 to 11; Preferably, during the primary co-precipitation reaction, the concentration of the complexing agent in the solution in the reactor is 7 to 11 g / L; Preferably, the primary coprecipitation reaction is carried out under stirring, Preferably, the stirring speed of the primary coprecipitation reaction is 300 to 380 r / min; Preferably, the time for the primary coprecipitation reaction is 60 to 90 h; Preferably, before the primary coprecipitation reaction, deionized water, the complexing agent solution and the precipitating agent solution are first added to the reaction apparatus to prepare a base solution for the primary coprecipitation reaction. The preparation method according to any one of claims 6 to 10.

12. The second metal salt mixed solution is prepared by mixing a nickel salt, a manganese salt, and a solvent, or the second metal salt mixed solution is prepared by mixing an iron salt, a manganese salt, and a solvent, Preferably, the total concentration of metal ions in the second metal salt mixed solution is 1 to 4 mol / L; Preferably, the molar ratio of the nickel salt to the manganese salt is a:(1-a), or the molar ratio of the iron salt to the manganese salt is a:(1-a), with 0.05≦a≦0.7; Preferably, the nickel salt comprises any one of nickel sulfate, nickel chloride, or nickel nitrate; Preferably, the iron salt comprises ferrous sulfate or ferrous chloride; Preferably, the manganese salt comprises any one of manganese sulfate, manganese chloride or manganese nitrate; Preferably, the solvent comprises deionized water; Preferably, in the secondary coprecipitation reaction, the second metal salt mixed solution is injected into the reactor at a flow rate of 8 to 12 kg / h; Preferably, in the secondary coprecipitation reaction, the complexing agent solution is injected into the reactor at a flow rate of 1 to 3 kg / h; Preferably, in the secondary coprecipitation reaction, the precipitant solution is injected into the reactor at a flow rate of 2.4 to 3 kg / h; Preferably, the secondary co-precipitation reaction is carried out at 40 to 60° C. Preferably, during the secondary co-precipitation reaction, the pH of the solution in the reactor is 8.5 to 11; Preferably, during the secondary co-precipitation reaction, the concentration of the complexing agent in the solution in the reactor is 8-12 g / L; Preferably, the secondary co-precipitation reaction is carried out under stirring; Preferably, the stirring speed of the secondary coprecipitation reaction is 250 to 350 r / min; Preferably, the time of the secondary coprecipitation reaction is 2 to 8 h. The preparation method according to any one of claims 6 to 11.

13. A positive electrode material, The positive electrode material is prepared from a positive electrode material precursor according to any one of claims 1 to 5, The positive electrode material includes an O3 phase core and a P2 phase shell surrounding the O3 phase core, and the O3 phase core is Na(Ni x Fe y Mn 1-x-y ) O 2 where 0.2≦x≦0.7 and 0.2≦y≦0.5, and the P2 phase shell is Na b (M a Mn 1-a ) O 2 wherein M is nickel or iron, 0.05≦a≦0.7, and 0.67≦b≦0.78; and the O3 phase core and the P2 phase shell are both deposited in flake-shaped primary particles. Positive electrode material.

14. mixing a positive electrode material precursor, a dispersant and a sodium source, and then calcining the mixture to obtain the positive electrode material; A method for preparing the positive electrode material of claim 13.

15. The dispersing agent comprises polyvinylpyrrolidone; Preferably, the sodium source comprises sodium carbonate; Preferably, the positive electrode material precursor, the dispersant and the sodium source are mixed by grinding in a mortar; Preferably, the firing temperature is 800 to 1000° C. Preferably, the baking time is 12 to 20 h.

15. The method of claim 14.

16. The cathode material of claim 13, Sodium ion battery.

Citation Information

Patent Citations

  • Positive electrode active substance for nonaqueous electrolyte secondary cell, and nonaqueous electrolyte secondary cell

    CN109983604A

  • Core-shell structure sodium ion battery positive electrode material and preparation method and application thereof

    CN110277540A

  • High-nickel ternary precursor, positive electrode material and preparation method thereof

    CN112250091A

  • Continuous production method and device for in-situ doping of high-nickel ternary positive electrode material precursor of lithium ion battery

    CN113387400A

  • Composite positive electrode material and preparation method thereof

    CN113991079A

Cited By

  • Positive electrode active material for sodium secondary batteries, positive electrode for sodium secondary batteries, and sodium secondary batteries

    JP7917236B1